Application of dermoscopy image analysis technique in diagnosing urethral condylomata acuminata - Yunjie Zhang; Shuang Jiang; Hui Lin; Xiaojuan Guo; Xianbiao Zou (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: In this study, cases with suspected urethral condylomata acuminata were examined by dermoscopy, in order to explore an effective method for clinical. Objective: To study the application of dermoscopy image analysis technique in clinical diagnosis of urethral condylomata acuminata. Methods: A total of 220 suspected urethral condylomata acuminata were clinically diagnosed first with the naked eyes, and then by using dermoscopy image analysis technique. Afterwards, a comparative analysis was made for the two diagnostic methods. Results: Among the 220 suspected urethral condylomata acuminata, there was a higher positive rate by dermoscopy examination than visual observation. Study limitations: Dermoscopy examination technique is still restricted by its inapplicability in deep urethral orifice and skin wrinkles, and concordance between different clinicians may also vary. Conclusion: Dermoscopy image analysis technique features a high sensitivity, quick and accurate diagnosis and is non-invasive, and we recommend its use.